Optimalisasi Pemanfaatan Media Sosial dan Artificial Intelligence untuk Karang Taruna Kalibaru - Bernadus Gunawan Sudarsono; Alexius Ulan Bani; Sharyanto; Joko Saputro; Raditya Galih Whendasmoro (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Global economic dynamics and the acceleration of digital transformation require youth organizations and local micro-businesses to adopt adaptive marketing communication strategies. Youth organizations in Karang Taruna (Youth Organization) hold a strategic position as a driving force for the community economy, but the sustainability of their businesses and organizational activities is often hampered by limited digital literacy, inconsistent content production, and the lack of a structured marketing strategy. This community service program aims to optimize the digital capacity of youth organizations in Kalibaru Village, Cilincing District, North Jakarta, through training in social media mastery and the integration of Artificial Intelligence (AI) technology based on an output-driven approach. The methods applied include qualitative-descriptive situational analysis, conceptual education delivery, hands-on workshops on AI prompt development and visual design, mentoring for independent publications, and integrated qualitative evaluation. The results of the activity showed significant improvements in participants' conceptual understanding and practical skills. All groups successfully designed persuasive copywriting, created proportional visual designs, and uploaded digital promotional content in real time to social media platforms. The use of AI tools has been proven to significantly reduce production time and streamline workflows without requiring a large financial investment. This program demonstrates that accelerating the adoption of artificial intelligence based on prompt engineering can strengthen the competitiveness, creativity, and economic independence of youth in densely populated urban areas.